Strengthening Evaluation of Physical Fitness, Health, and Movement Competency - Adi S; Tommy Soenyoto; Cahyo Yuwono; Sri Indah Ihsani; Made Bang Redy Utama; Supriyono Supriyono (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2025)
The high number of students who are physically inactive and the limitations of Physical Education teachers in conducting fitness evaluations indicate the need for competency improvement through structured training. Many teachers do not yet understand the concept of physical literacy and are not skilled in using valid and reliable fitness measurement tools. This community service activity aims to enhance the ability of PJOK teachers to measure and evaluate the fitness, health index, and physical literacy of students through a data-based approach. The methods of the activity include coordination with stakeholders, material preparation, pretest, theoretical and practical training (classroom, demonstration, case study, field practice), posttest, and result evaluation. The instrument used is a Google Form questionnaire developed to measure teachers' understanding and skills before and after the training. The results show a significant improvement: conceptual understanding increased from 28% to 88%, the skill in using measurement tools increased from 22% to 85%, and data analysis ability increased from 15% to 82%. In conclusion, the PEFORMA training is effective in equipping teachers with essential competencies to support the objective, systematic, and sustainable evaluation of student fitness. This program is recommended/advised to be implemented more widely as part of strengthening the quality of physical education in elementary schools.